Weighting the impact of virulence on the outcome of Pseudomonas aeruginosa bloodstream infections. (March 2020) - Sánchez-Diener, I.; Zamorano, L.; Peña, C.; Ocampo-Sosa, A.; Cabot, G.; Gómez-Zorrilla, S.; Almirante, B.; Aguilar, M.; Granados, A.; Calbo, E.; Rodriguez-Baño, J.; Rodríguez-López, F.; et al.
ABSTRACT: Objectives: We assessed the association between the lethality of Pseudomonas aeruginosa in a Caenorhabditis elegans model and outcomes of P. aeruginosa bloodstream infections. Methods: A total of 593 P. aeruginosa bloodstream isolates recovered from a prospective Spanish multicentre study were analysed. Clinical variables, susceptibility profiles and Type III Secretion System (TTSS) genotypes ( exoU / exoS genes) were available from previous studies. A C. elegans virulence score (CEVS) was used, classifying the isolates into high (CEVS 4–5), intermediate (CEVS 3) and low (CEVS 1–2) virulence. The main outcome analysed was 30-day mortality. Results: Up to 75% (446/593) of the isolates showed a high-virulence phenotype, and 17% (101/593) a low-virulence one. No association between virulence phenotype and the main outcome variable (30-day mortality) was found (29/101 (28.7%) versus 127/446 (28.5%), p 1). However, an inverse association between C. elegans virulence and multidrug-resistant and extensively drug-resistant profiles was documented (OR 0.655 (95% CI 0.571–0.751) and OR 0.523 (95% CI 0.436–0.627), p <0.001, respectively), whereas the exoU genotype was significantly more frequent among isolates showing high virulence (10/101 (9.9%) versus 112/446 (25.1%), p <0.001). Moreover, although significance was not reached, strains showing a high-virulence phenotype tended to be associated with community-acquired infections (1/101 (1%) versus 25/446 (5.6%), p 0.065), whereas low-virulence phenotypes tended to be associated with a higher illness severity (such as higher median Pitt score: 2 (1–4) versus 1 (0–3), p 0.036, or initial multiorgan dysfunction: 17/101 (16.8%) versus 41/446 (9.2%), p 0.024), with some underlying conditions (such as chronic renal failure 24/101 (23.8%) versus 59/446 (13.2%), p 0.013), and with the respiratory source of infections (17/101 (16.8%) versus 45/446 (10.1%), p 0.058). Conclusions: Our results indicate that the P. aeruginosa virulence phenotype in a C. elegans model correlates with virulence genotype (TTSS) and resistance profile, but it is a poor prognostic marker of mortality in bloodstream infections.